Catastrophic sickling crisis in patient undergoing cardiac transplantation with sickle cell trait. Issue 8 (30th April 2019) - Ali, Jason M.; Besser, Martin; Goddard, Martin; Abu‐Omar, Yasir; Catarino, Pedro; Bhagra, Sai; Berman, Marius
Abstract : There is debate in the literature regarding management of patients with sickle cell trait (SCT) undergoing cardiac surgery, since it is recognized that cardiopulmonary bypass presents many precipitating risk factors for a sickling crisis. Despite this, many report successful outcomes without any modification to perioperative management. A 49‐year‐old woman with SCT (HbS 38%) with postpartum cardiomyopathy underwent cardiac transplantation. The patient was cooled to 34.0°C and retrograde cold blood cardioplegia was infused continuously. The cold ischemic time was 219 minutes and warm ischemic time 46 minutes. After weaning from bypass, she developed global cardiac dysfunction requiring veno‐arterial extracorporeal membrane oxygenation. The circuit suddenly stopped, requiring emergency reinstitution of bypass; the circuit had clotted. Transesophageal‐echocardiogram revealed thrombus within the left atrium and ventricle. There was no recovery of cardiac function and the patient developed multiorgan failure. At postmortem there was extensive myocardial infarction with evidence of widespread catastrophic intravascular red‐cell sickling. This case highlights the danger of complacency in patients with SCT, offering a learning opportunity for the cardiothoracic community to highlight the most serious complication that can occur in this group of patients. We have learned that SCT and cardiac surgery is not a benign combination. Abstract : The authors describe a patient with a sickle cell trait in which a catastrophic sickling crisis occurred immediately following heart transplantation, ultimately resulting in death.